Fusarium citri-sinensis sp. nov. (Ascomycota: Nectriaceae) isolated from fruit of Citrus sinensis in China - Zhao, Lin; Wei, Xin; Huang, Cheng-Xin; Yi, Ji-Ping; Deng, Jian-Xin; Cui, Meng-Jiao (Phytotaxa, 2022)
During an investigation of fungal pathogens associated with Citrus sinensis in Zigui county of Yichang city, China, a new species, Fusarium citri-sinensis sp. nov. was isolated from fruit of C. sinensis. The species is described using morphology and molecular multi-locus analyses based on a combined data of internal transcribed spacer region of the rDNA (ITS), translation-elongation factor 1 alpha (EF-1α), and RNA polymerase second largest subunit (RPB2) genes. It is one of the species in Fusarium lateritium species complex (FLSC).